Teknologi Digital : Pengaruhnya terhadap Efektifitas Manajemen Sumber Daya Insani Bank Syariah di Tanah Datar - Wahyuni, Elmiliyani; Asmawanti, Dri (Al-bank: Journal of Islamic Banking and Finance, 2025)
The purpose of this study was to determine the effect of digital technology on Human Resource Management at Islamic Banks in Batusangkar, both aspects of recruitment, performance appraisal, training and employee development. The research method uses mixed method with sequential exploratory model by combining qualitative and quantitative research methods sequentially. The first stage of the research was carried out qualitative methods and in the second stage quantitative. The results of this study indicate that digital technology has a significant influence on Islamic banking SDI management. Digital transformation not only increases efficiency and transparency, but also accelerates decision-making and improves workforce quality through technology-based training. However, for the impact of digitalization to be optimized, Islamic banking needs to adopt a decentralized strategy in SDI management and improve digital literacy for all employees. This will ensure that digital technology is not only a supporting tool, but also an integral part of a more innovative and adaptive SDI management strategy.